Somatic embryogenesis and shoot organogenesis in peanut cv. 'Georgia-12Y' and successful transfer to the soil. - Poonam Khatri; Nirmal Joshee (PLoS ONE)
An efficient regeneration system was established through somatic embryogenesis and shoot organogenesis using mature embryos explants of peanut cultivar 'Georgia-12Y'. The role of plant growth regulator combinations was investigated for embryogenic callus and somatic embryo induction. Results showed that Murashige and Skoog (MS) medium supplemented with 20 μM picloram (4-amino 3, 5, 6-trichloropicolinic acid), casein hydrolysate (0.2 g/L), sucrose (30 g/L) and sorbitol (10 g/L) supported callus induction in dark and higher number of somatic embryos in light. No somatic embryos were induced at 0.1 μM to 10.0 μM of 2,4-Dichloro phenoxy acetic acid (2,4-D) and picloram individually. The highest regeneration frequency of 90% was recorded on 40 μM 2,4-D + casein hydrolysate (0.2 g/L), sucrose (30 g/L) and sorbitol (10 g/L). The plantlets regenerated via somatic embryogenesis did not exhibit any morphological abnormalities. Double staining with acetocarmine and Evans blue distinguished between embryogenic and non-embryogenic callus. Histological observations confirmed distinct developmental stages of somatic embryos. On the other hand, highest number of shoots were induced in response to MS + 15 μM thidiazuron (TDZ) among various treatments tested. Incubation of shoots on plant growth regulator free MS medium induced in-vitro flowering after 12 weeks under light conditions. The induction of embryogenic and morphogenic callus and production of fertile peanut plants using manipulations of various plant growth regulators is reported on peanut cultivar 'Georgia- 12Y'.